2015
DOI: 10.3168/jds.2014-9116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pleurotus eryngii polysaccharides on bacterial growth, texture properties, proteolytic capacity, and angiotensin-I-converting enzyme–inhibitory activities of fermented milk

Abstract: Pleurotus eryngii is one of the most favored oyster mushrooms and contains various beneficial bioactive compounds. Polysaccharide extracted from P. eryngii (PEPS) was added as a natural-source ingredient to milk before fermentation, and the effects of additional PEPS on fermented milk were investigated in this study. The PEPS were extracted and added to reconstituted skim milk (12%, wt/vol) at 0.5, 0.25, and 0.125% (wt/vol) and fermented by a non-exopolysaccharide-producing strain, Streptococcus thermophilus A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 34 publications
(46 reference statements)
2
23
0
Order By: Relevance
“…The data showed no significant correlation between EPS concentration and level of whey syneresis or WHC, which suggested that the effect of EPS may be related to the physical and chemical properties of the EPS which are determined by molecular mass and subunit structure, in addition to the interaction between EPS and milk protein. It has been reported that Pleurotus eryngii polysaccharides could accelerate spontaneous whey separation of fermented milk, which could be as a result of the protein aggregation and decreased casein in milk led by the addition of P. eryngii polysaccharides (Li & Shah, ). In our study, the different effects of YS108R and C11A10B may be due to the individual properties of the EPS produced by each strain, which may interact with milk protein in a different manner and then affects the gel structure.…”
Section: Resultsmentioning
confidence: 99%
“…The data showed no significant correlation between EPS concentration and level of whey syneresis or WHC, which suggested that the effect of EPS may be related to the physical and chemical properties of the EPS which are determined by molecular mass and subunit structure, in addition to the interaction between EPS and milk protein. It has been reported that Pleurotus eryngii polysaccharides could accelerate spontaneous whey separation of fermented milk, which could be as a result of the protein aggregation and decreased casein in milk led by the addition of P. eryngii polysaccharides (Li & Shah, ). In our study, the different effects of YS108R and C11A10B may be due to the individual properties of the EPS produced by each strain, which may interact with milk protein in a different manner and then affects the gel structure.…”
Section: Resultsmentioning
confidence: 99%
“…This has promoted, especially in the past years, an increasing interest in extracting ingredients from foods such as mushrooms and in developing functional foods (Li & Shah, 2015). polysaccharides, small peptides and proteins) and low (e.g.…”
Section: Isolated Compounds and Bioactivitymentioning
confidence: 99%
“…Pleurotus eryngii is a kind of favored oyster mushroom, and contains rich nutrients, such as protein, fiber, carbohydrates, vitamins and minerals (Cohen et al 2002; Li and Shah 2015). Li and Shah (2015) found that polysaccharide extracted from P. eryngii could promote the proliferation of Streptococcus thermophilus in fermented milk, and enhance its viability rate during refrigerated storage at 4 °C (Li and Shah 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Li and Shah (2015) found that polysaccharide extracted from P. eryngii could promote the proliferation of Streptococcus thermophilus in fermented milk, and enhance its viability rate during refrigerated storage at 4 °C (Li and Shah 2015). In the previous study, we found that L. lactis subsp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation